2017
DOI: 10.1002/pd.5031
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and nitric oxide synthase induction by surgical uteroplacental circulation restriction in the rabbit fetal heart

Abstract: Objective This study investigated the role of oxidative damage and nitric oxide (NO) synthases in the fetal heart using a model of intrauterine growth restriction induced by uteroplacental circulation restriction (UCR).Methods New Zealand white rabbits kept under 12-h light cycles, with food and water provided ad libitum, were subjected at day 25 of pregnancy to 40-50% uteroplacental artery ligation. We analyzed the gene expression of enzymes linked to nitric oxide synthesis (iNOS, eNOS, HO-1, and ARG-2), hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Some studies show increased eNOS in the carotid artery and decreased in the femoral artery [ 57 ] at the protein and gene expression levels [ 59 ]. In the heart, eNOS expression was increased at the protein and decreased at the gene expression level [ 85 ]. The effect of hypoxia on eNOS expression depends on the duration of hypoxia because increased ROS production may interfere with the bioavailability of NO during prolonged hypoxia [ 58 ].…”
Section: Prenatal Hypoxiamentioning
confidence: 99%
“…Some studies show increased eNOS in the carotid artery and decreased in the femoral artery [ 57 ] at the protein and gene expression levels [ 59 ]. In the heart, eNOS expression was increased at the protein and decreased at the gene expression level [ 85 ]. The effect of hypoxia on eNOS expression depends on the duration of hypoxia because increased ROS production may interfere with the bioavailability of NO during prolonged hypoxia [ 58 ].…”
Section: Prenatal Hypoxiamentioning
confidence: 99%
“…Moreover, Figueroa H. et al, using New Zealand rabbits exposed to fetal hypoxia, showed an increased dilation of the vessels in fetal hearts. The authors justified this results with an increase in the activity of eNOS, inducible nitric oxide synthase (iNOS) and of the levels of carbonyl proteins, suggesting that oxidative stress is an important stimulus to initiate adverse effects in fetal hearts [48].…”
Section: Animal Models Of Prenatal Hypoxiamentioning
confidence: 91%
“…The kidneys were fixed in 10% buffered formalin, embedded in paraffin, sectioned, dewaxed, rehydrated, rinsed in water, and stained with hematoxylin and eosin and periodic acid Schiff (PAS). The morphologic analysis was carried out in a blinded manner as detailed previously [23,28]. The cortex and medulla were evaluated for epithelial necrosis, loss of brush border, tubular dilation, and tubular congestion among other kidney alterations observed in response to AKI.…”
Section: Histochemical Analysis and Tissue Damage Determinationmentioning
confidence: 99%
“…Western blot was realized as was previously published with some modifications [27][28][29]. Briefly, the renal cortex and medulla were dissected and homogenized with an Ultra-Turrax homogenizer in ice-cooled 10 mM Tris•HCl buffer at pH 7.4, supplemented with 1 mM EDTA, 1 mM EGTA, 0.25 M sucrose, 1% vol/vol Triton X-100, and a protease inhibitor cocktail (Complete Mini, Roche Applied Science).…”
Section: Western Blot Assaymentioning
confidence: 99%